+0  
 
-1
295
1
avatar+3371 

Help.

NotSoSmart  Apr 3, 2017
 #1
avatar+89704 
+2

8.  (x + 6)^2 + (y - 7)^2  = 81

 

9.  The radius  = sqrt [ (-6 - 0)^2 + ( -8 - 0)^2 ] =  sqrt (100) = 10

 

So...the equation is   (x + 6)^2 + (y + 8)^2  = 100

 

 

10.  We have

 

( 3 - h)^2 + ( -1 - 7)^2  = 100  simplify

 

3^2 - 6h  + h^2 + 64  = 100

 

h^2 - 6h + 73  = 100

 

h^2 - 6h - 27  = 0     factor 

 

(h - 9) ( h + 3)  = 0

 

Setting each factor to 0  and solving for h  we have that  h = 9 or h = -3

 

 

cool cool cool

CPhill  Apr 3, 2017

10 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.